Design of optical fiber based functional devices for imaging applications - Sun, Chengyu. (2013)
In this project, a double clad fiber coupler (DCFC) has be designed and optimized for enhanced performance of imaging applications. Two methods of coupler design have been studied – side polished optical fiber based DCFC and V-groove optical fiber based DCFC. By using R-soft CAD and Matlab software, the author construct the structure and simulations have been carried out. Factors such as polished depth, V-groove depth, V-groove angle, and wavelength effect have been discussed as well.